Pendampingan Digital Marketing untuk Meningkatkan Kemampuan Komunikasi Pemasaran Masyarakat Kelurahan Dwikora dalam Memasarkan Produk UMKM - Eva Margareth Sarah; Niscaya Hia; Dewi Ervina Suryani; Pelita Telaumbanua; Ludovikus Defianto Bazikho (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The digital era continues to evolve and bring innovation and change to various industries. Through digital transformation and strategies needed to overcome obstacles in the digital era, organizations can adapt and change. To achieve their goals, MSMEs must implement efficient marketing techniques in their operations. This community service method uses the PAR (Participatory Action Research) technique. This is in line with the conditions of the partner, Dwikora Village, which has human resources that are well known to both village officials and residents. The results found that due to a lack of understanding of digital marketing communication management procedures, they were unfamiliar with digital marketing techniques, different social media platforms, or how to measure their effectiveness. The Community Service Team conveyed their understanding of the importance of digital marketing communication in improving the knowledge and skills of residents as an effort to improve their marketing communication skills. This was because many residents, especially mothers, did not understand how to use digital marketing to promote their MSMEs. The team formed a content creation team or digital marketing communication managers, socialized the value of digital marketing communication to the sub-district residents in improving their knowledge and skills, and implemented a digital marketing communication message management strategy on Instagram. After these activities, partners can create interesting and relevant content that suits the interests of the target audience in Dwikora Village, namely its residents.